1990
DOI: 10.1007/bf02780343
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of central cholinergic mechanisms and neuroadaptation to nicotine

Abstract: This review focuses on neuroadaptation to nicotine. The first part of the paper delineates some possible general mechanisms subserving neuroadaptation to commonly abused drugs. The postulated role of the mesocorticolimbic neuroanatomical pathway and drug-receptor desensitization mechanisms in the establishment of tolerance to, dependence on, and withdrawal from psychoactive drugs are discussed. The second part of the review deals with the pharmacological effects of nicotine at both pre- and postsynaptic locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 214 publications
0
40
0
Order By: Relevance
“…Of significance is the finding that in the repeated reinstatement tests, cue-induced reinstatement of nicotine-seeking was obtained only at the two highest doses of nicotine. The explanation for the difference between higher nicotine dose groups and the lower one may reside in neuroadaptive changes that accrue after chronic high level of nicotine exposure (Ochoa et al 1990;Miyata and Yanagita 2001;Rahman et al 2004). For example, it has been found that after 25 daily 1-h nicotine (0.03 mg/kg/infusion) self-administration sessions, rats had decreased basal dopamine levels in the nucleus accumbens and a blunted dopamine increase in response to nicotine challenge (Rahman et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Of significance is the finding that in the repeated reinstatement tests, cue-induced reinstatement of nicotine-seeking was obtained only at the two highest doses of nicotine. The explanation for the difference between higher nicotine dose groups and the lower one may reside in neuroadaptive changes that accrue after chronic high level of nicotine exposure (Ochoa et al 1990;Miyata and Yanagita 2001;Rahman et al 2004). For example, it has been found that after 25 daily 1-h nicotine (0.03 mg/kg/infusion) self-administration sessions, rats had decreased basal dopamine levels in the nucleus accumbens and a blunted dopamine increase in response to nicotine challenge (Rahman et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, in understanding the neurobiology of nicotine reinforcement it is necessary to consider an important effect of nicotine that occurs at the nicotinic acetylcholine receptor (nAChR). A vast literature demonstrates that after initial activation, nAChRs rapidly desensitize and the duration of this inactivation varies according to the sub-unit composition of the receptor (Ochoa et al 1990;Rosecrans and Karan 1993;. In light of this effect it has remained a paradox that heavy smokers, with fairly high circulating blood-levels of nicotine (Rose et al 1999), demonstrate persistent smoking each day.…”
Section: The Neurobiology Of Nicotine Reinforcementmentioning
confidence: 99%
“…Association of a-and non-a-subunits into a pentameric oligomer is considered as necessary for function (Cooper et al 1991;Anand et al 1991), with the notable exception of the a7 subunit from chick brain which forms functional homooligomers in Xenopus oocytes (Couturier et al 1990 a). Different assemblies of neuronal nicotinic receptor subunits yield, in Xenopus oocytes, functional receptors with different affinities for acetylcholine and different pharmacological specificities (for review Luetje et al 1990;Ochoa et al 1992). At this stage, the actual subunit composition of nicotinic receptors in the brain is largely unknown and the occurrence of pharmacologically non-equivalent (or equivalent) acetylcholine binding sites has not been demonstrated.…”
Section: The Diversity Of Nicotinic Receptor Sitesmentioning
confidence: 99%
“…Prolonged exposure of muscle, electroplaque and brain nicotinic acetylcholine receptor to agonists causes, within seconds to minutes, a reversible decline in the ionic response to acetylcholine (Katz & Thesleff, 1957, Changeux, 1980Ochoa et al 1989Ochoa et al , 1992. Desensitization persists after purification of excitable membranes (Popot et al 1974) and after reconstitution of the purified protein (Popot et al 1981;McNamee & Ochoa, 1982;Montal et al 1986).…”
Section: Regulation By Desensitization Of the Permeability Response Tmentioning
confidence: 99%
See 1 more Smart Citation